2015
DOI: 10.3926/jiem.1400
|View full text |Cite
|
Sign up to set email alerts
|

Research on evaluation of enterprise project culture based on Denison model

Abstract: Abstract:Purpose: The purpose of this paper is to build enterprise project culture evaluation model and search for the best evaluation method for Chinese enterprise project culture on the basis of studying and drawing lessons from enterprise culture evaluation theory and method at home and abroad. evaluation model and scale structure also need to be improved, but the thinking of this paper in this field provides a valuable reference for future research.Practical Implications: This paper provides the support of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…All of these characteristics allow identification of the gaps between optimal performance (Y. Zeng, Jin, Guo, & Zhang, 2015) in terms of the three typical hierarchical levels within the business environment and, specifically, within the organization studied here. The survey was applied to a sample of 163 of the supermarket's workers, of whom seven pertain to the strategic level, 26 to the executive level, and 130 to the operational level.…”
Section: Methodsmentioning
confidence: 99%
“…All of these characteristics allow identification of the gaps between optimal performance (Y. Zeng, Jin, Guo, & Zhang, 2015) in terms of the three typical hierarchical levels within the business environment and, specifically, within the organization studied here. The survey was applied to a sample of 163 of the supermarket's workers, of whom seven pertain to the strategic level, 26 to the executive level, and 130 to the operational level.…”
Section: Methodsmentioning
confidence: 99%
“…Project risk culture can be defined as a unique occurrence 'showing' how team members and other project stakeholders perceive and understand particular project risks. The above approach is based on and results from these individuals' values, expectations and beliefs [66]. It is also influenced by the understanding and knowledge these individuals have about particular project risks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both SPC and EPC attempt to popularize MBP and build a project culture to ensure sustainable development and achieve organization strategic objectives with the MBP application. Hence, it can be concluded that the EPC characteristics can provide a reference for defining SPC [55], which enables SPC to be analyzed from three aspects, i.e., scope, purpose, and result, and the definition of SPC can be described as follows.…”
Section: Connotation Of Social Project Culturementioning
confidence: 99%